2023
DOI: 10.1021/acs.jpcb.3c01125
|View full text |Cite
|
Sign up to set email alerts
|

Large Decrease in the Melting Point of Benzoquinones via High-n Eutectic Mixing Predicted by a Regular Solution Model

Abstract: Decreasing the melting point (T m ) of a mixture is of interest in cryopreservatives, molten salts, and battery electrolytes. One general strategy to decrease T m , exemplified by deep eutectic solvents, is to mix components with favorable (negative) enthalpic interactions. We demonstrate a complementary strategy to decrease T m by mixing many components with neutral or slightly positive enthalpic interactions, using the number of components (n) to increase the entropy of mixing and decrease T m . In theory, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Though the total concentration reached 3.5 M, the mixed electrolyte approach effectively dilutes each component by a factor of 2, limiting the maximum concentration that can be achieved. Redox-inactive deep eutectic solvents have also been investigated. In these systems the redox-active species is not a eutectic component, resulting in similar limitations to other solvent-led approaches, including low solubility of redox-active species and high viscosity …”
Section: Eutectic Electrolytes In Flow Batteriesmentioning
confidence: 99%
“…Though the total concentration reached 3.5 M, the mixed electrolyte approach effectively dilutes each component by a factor of 2, limiting the maximum concentration that can be achieved. Redox-inactive deep eutectic solvents have also been investigated. In these systems the redox-active species is not a eutectic component, resulting in similar limitations to other solvent-led approaches, including low solubility of redox-active species and high viscosity …”
Section: Eutectic Electrolytes In Flow Batteriesmentioning
confidence: 99%
“…Zhang et al 22 used this method to design Li-ion electrolytes that remained in the liquid phase as low as −130 °C, while Cho et al 23 utilized the same calculation to develop carbonate–nitrile Li-ion electrolytes capable of maintaining the liquid form down to −110 °C. The method has also been used to predict eutectic points in benzoquinones 24 and many other solvents. 25 Similarly, work by Schoetz et al 7 on IL electrolytes for Al batteries has shown that increasing the entropy of the liquid phase has general success in depressing the freezing point.…”
Section: Introductionmentioning
confidence: 99%